Pellet production from furfural residue and sawdust: Evaluating the characteristics and quality of pellets and their dependency on process parameters. (June 2021) - Siyal, Asif Ali; Mao, Xiao; Liu, Yang; Ao, Wenya; Jiang, Zhihui; Wahab, Nasrul; Ran, Chunmei; Zhang, Ruihong; Liu, Guangqing; Dai, Jianjun
Abstract: A single pellet press was employed for production of furfural residue pellets (FRPs) and wood pellets (WPs). The effects of temperature (70–200 °C), pressure (70–160 MPa), moisture content (MC) (5.5–28%), particle size (0.25–0.5 and 0.5–1.41 mm) and a binder on the physical and mechanical characteristics and energy consumption of FRPs and WPs were investigated. Temperature and pressure were found to be the most dominant factors followed by MC and particle size. For FRPs, pellet density, strength and hardness increased with increasing temperature from 70 to 130 °C and increasing pressure from 70 to 160 MPa and then decreased at >130 °C and a MC of 5.5%. The highest particle density of ~1.43 g cm −3, strength >8 and 5.56 MPa, hardness 438.5 and 350.2 N mm −2 for particles 0.25–0.5 and 0.5–1.41 mm, respectively, was found at 130 °C, 160 MPa and 5.5% MC. For WPs, the highest pellet density, strength and hardness were achieved at 200 °C, ≥100 MPa. FRPs and WPs remained dimensionally stable particularly at temperature ≥130 °C, pressure 160 MPa and 5.5% MC. For a MC of 5.5%, pellets made at 200 °C were found to be water resistive. Increasing temperature, MC and use of a binder reduced the energy consumption of FRPs and WPs. Use of a binder was more beneficial for WPs compared to FRPs. FRPs had better quality and lower energy consumption than WPs. Temperatures of 130 °C and 200 °C, particle size of 0.25–0.5 mm and MC of 5.5% and 18% were found to be optimal for FRPs and WPs quality. Highlights: Higher density, strength and hardness and lower SEC of FRPs were achieved at 130 °C. FRPs were 14.8–16.8% denser, 52–74.12% stronger and 88–227.8% harder than WPs. SEC of FRPs were 4.2–16.3% (0.25–0.5 mm) and 16.6–31% (0.5–1.41 mm) lower than WPs. Use of binder was more beneficial for WPs compared to FRPs. At 200 °C FRPs were found resistive to water penetration without any disintegration.